Very high upper critical fields and enhanced critical current densities in Nb3Sn superconductors based on Nb–Ta–Zr alloys and internal oxidation. (9th March 2021) - Buta, F; Bonura, M; Matera, D; Bovone, G; Ballarino, A; Hopkins, S C; Bordini, B; Chaud, X; Senatore, C
Abstract: The inhibition of Nb3 Sn grain growth in the presence of ZrO2 nanoparticles appears to be one of the most promising method for pushing the critical current densities of Nb3 Sn superconducting wires to levels that meet the requirements set for the Future Circular Collider. We have investigated the effect of ZrO2 nanoparticles formed by the internal oxidation of Zr on the superconducting properties and microstructure of Nb3 Sn formed from Nb-1 wt%Zr, Nb-7.5 wt%Ta, Nb-7.5 wt%Ta-1 wt%Zr and Nb-7.5 wt%Ta-2 wt%Zr alloys. A monofilamentary wire configuration was used, with a 0.22 mm outer diameter Nb-alloy tube containing a core of powdered metal oxide (SnO2, CuO or MoO3 ) as oxygen source and successive deposits of Cu, Sn and Cu on the outer surface. As determined from inductive measurements, the layer critical current densities of the samples based on Nb alloys with internally oxidized Zr were superior to those based on Nb-7.5 wt%Ta. The samples based on Nb-7.5 wt%Ta-1 wt%Zr and Nb-7.5 wt%Ta-2 wt%Zr showed higher critical current densities at high magnetic fields (above 10–15 T), and upper critical fields exceeding 28.5 T at 4.2 K (99% normal state resistivity criterion). A record value of 29.2 T of the upper critical field at 4.2 K was obtained on samples based on Nb-7.5 wt%Ta-2 wt%Zr. Hypotheses are proposed and discussed for explaining this unexpected increase of the upper critical field, by considering the possible effects of non-oxidized Zr on the superconducting properties of Nb3 Sn and of the oxidized Zr on the formation and microchemistry of Nb3 Sn. Regardless of sample type the Nb3 Sn grains observed in our samples have an aspect ratio of 1.5–1.7. When compared in the short axis direction, the mean distance between grain boundary intercepts (lineal intercept method) is ∼40% smaller in the samples with internally oxidized Zr than in the reference samples based on Nb-7.5 wt%Ta. In the long axis direction the reduction is of 20%–30%.